DYNAMICS OF FORMATION AND DEVELOPMENT OF DEPRESSIVE AND COGNITIVE DISORDERS IN PATIENTS AFTER CEREBRAL STROKE - V. B. Mikhaylov; I. V. Zdesenko (Acta Biomedica Scientifica, 2014)
Features of clinical structure, regularities of formation, development and course of depressive and cognitive disorders in patients after cerebral stroke were determined. In patients with cerebral stroke the disorder of state of consciousness with cognitive and asthenic disorders with further formation of psychoemotional disorders with elements of hypochondria on the background of remaining cognitive disorders are primary.